Training Needs of Agricultural Supervisors in Jaipur District of Rajasthan - Choudhary, L. R.; Sharma, N.K.; Dangi, K.L. (Indian Journal of Extension Education, 2012)
The present investigation was carried out in Jaipur district of Rajasthan. Thirty per cent agricultural supervisors from each  of the thirty panchayat samities constituted the total sample of 67. They were drawn from each panchayat samiti through  random sampling technique. Face - to - face method of interview was employed for data gathering. Emperical findings of  the study revealed that supervisors needed in-service training in order of priority in the areas like drip irrigation systems  and water saving techniques in agriculture, sprinkler irrigation, preparation of farm production, plan and budgeting,  dryland farming, pests and diseases control in high yielding varieties, soil moisture conservation techniques, extension  and communication techniques, fertilizer and their application in high yielding varieties (HYVs), package of practices of  HYVs evaluation techniques, vegetables and fruits preservation for off-season, crop rotation and intercultural operations,  soil and seed treatment, organic farming to enhance the qualitative agriculture production without degradation in soil  environment. It is strongly recommended that the grass root level agricultural supervisors (VEWS) must be regularly  trained in the areas of water conservation and irrigation techniques.
Keywords: Drip irrigation; HYVs, In-service training; Agricultural supervisors